Five-fraction stereotactic radiosurgery (SRS) for single inoperable high-risk non-small cell lung cancer (NSCLC) brain metastases. Issue 1 (December 2015) - Lischalk, Jonathan; Oermann, Eric; Collins, Sean; Nair, Mani; Nayar, Vikram; Bhasin, Richa; Voyadzis, Jean-Marc; Rudra, Sonali; Unger, Keith; Collins, Brian
Abstract Background Achieving durable local control while limiting normal tissue toxicity with definitive radiation therapy in the management of high-risk brain metastases remains a radiobiological challenge. The objective of this study was to examine the local control and toxicity of a 5-fraction stereotactic radiosurgical approach for treatment of patients with inoperable single high-risk NSCLC brain metastases. Methods This retrospective analysis examines 20 patients who were deemed to have "high-risk" brain metastases. High-risk tumors were defined as those with a maximum diameter greater than 2 cm and/or those located within an eloquent cortex. Patients were evaluated by a neurosurgeon prior to treatment and determined to be inoperable due to tumor or patient characteristics. Patients were treated using the CyberKnife® SRS system in 5 fractions to a total dose of 30 Gy, 35 Gy, or 40 Gy. Results Twenty patients with a median age of 65.5 years were treated from April 2010 to August 2014 in 5 fractions to a median total dose of 35 Gy. At a median follow up of 11.3 months local tumor control was observed in 18 of 20 metastases (90 %). Both local failures were observed in patients receiving a lower dose of 30 Gy. Median pre-treatment dexamethasone dose was 10 mg/day and median post-treatment nadir dose was 0 mg/day. Salvage intracranial therapy was required in 45 % of patients. Symptomatic radionecrosis was observed in 4 of 20 patients (20 %), two of which were treated to 40 Gy and the remainder to 35 Gy. Kaplan-Meier 1-year, 2-year, and median survival were calculated to be 45 %, 20 %, and 13.2 months, respectively. Conclusions Five-fraction SRS to a total dose of 35 Gy appears to be a safe and effective management strategy for single high-risk NSCLC brain metastases, while a total dose of 40 Gy leads to an excess risk of neurotoxicity.